A Tale of Prosecutorial Indiscretion: Ramsey Clark and the Selective Non-Prosecution of Stokely Carmichael - Brown, Lonnie T. (2010)
During the height of the Vietnam War and one of the most volatile periods of the civil rights movement, then-Attorney General Ramsey Clark controversially resisted intense political pressure to prosecute Black Power originator and antiwar activist Stokely Carmichael. Taken in isolation, this decision may seem courageous and praiseworthy, but when considered against the backdrop of Clark’s contemporaneous prosecution of an all-white group of similarly situated anti-draft leaders (the so-called Boston Five), his exercise of prosecutorial discretion becomes suspect. Specifically, the Boston Five were prosecuted in 1968 for conspiracy to aid and abet draft evasion, a charge for which the evidence against Carmichael seemed markedly stronger. This article critically examines the propriety of Clark’s decision to forego the prosecution of Carmichael, and concludes that it was most likely the product of an earnest and unwavering commitment to the civil rights movement, generally, and the legally oppressed, specifically. Though objectively improper when analyzed alongside the prosecution of the Boston Five, Clark’s chosen course, which I ascribe to the exercise of prosecutorial indiscretion, is virtually impossible to condemn given his worthy motives and the singularly complex sociopolitical milieu within which he had to operate